LORD VOLDEMORT’S CHARACTER AANALYSIS IN J.K. ROWLING’S HARRY POTTER AND THE HALF BLOOD PRINCE - Radik Hermawan (STKIP PGRI Jombang, 2018)
This research is aimed to find the character type of Lord Voldemort as described in J.K. Rowling’s Harry Potter And The Half Blood Prince and the most dominant character of Lord Voldemort using a formalistic and psychological approach. The writer formulates the problem by making the following questions: (1) what are the characters type of Lord Voldemort in the Harry Potter and The Half Blood Prince novel?, (2) what is the dominant character of Lord Voldemort in the Harry Potter and The Half Blood Prince Novel?. In the process of study and analysis of the character type of the main characters in the Harry Potter and The Half Blood Prince novel, the writer uses a formalistic and psychological approach to analyze, examine and understand some of the main character's personality in a novel. The writer also conducts library research in completing this analysis. The theory used in analyzing the character until finally found one dominant character of the main character.